Neologisms and Their Functions in Critical Discourse - Storjohann, Petra (Lexikos, 2025)
The contributions of new words to the construction of a discourse are understood as discourse functions. For example, neologisms introduce new ways of thinking by embodying novel conceptual knowledge and influencing collective thought processes. They play a crucial role in distinguishing emerging social practices by clarifying vague concepts and laying the groundwork for further lexical innovation, such as through word formation. Within crisis-related discourse, neologisms become fundamental in shaping linguistic reality, acting as pivotal nodes within a structured network. They have the potential to expose ideological content and cultural values, as these terms can highlight key issues in debates. Terms such as Cancel Culture, Wokeness, and Greenflation capture a range of views and beliefs in societal dialogues across ideological, cultural, and political spectrums. However, when neologisms are documented lexicographically, their roles in discourse are not specified. This paper demonstrates how the key discourse aspects highlighted by new vocabulary are systematically documented in a recently developed German neologism dictionary. Clearly, the novel resource seeks to transcend the constraints of previous lexicographical methods by adopting specific elements of discourse lexicography (Kämper 2006: 350). This paper also explores whether new methods can be utilised for such an endeavour. Keywords: neologism resource, discourse lexicography, critical discourse analysis, discourse patterns, discourse functions, word embedding